Diseño de una Central Fotovoltaica de 1MW en el Cantón Zapotillo Utilizando el Software PVsyst. - Deivy Gonzalo, Ochoa Ruiz (2019)
The development of this research project allowed the design of a 1 MW photovoltaic plant, the scenario selected for the location of the same was Zapotillo canton, specifically the Saucillo sector for the solar radiation conditions existing in the place, making use of PVsyst software and national and international design standards governing the design, selection, sizing and construction of the components that make up the photovoltaic plants, the methodology used for design and sizing may be applicable to other scenarios if the database of the existing solar resource is available. The design of the photovoltaic plant consists of 4 004 photovoltaic modules, each with a nominal power of 250 kW. The purpose of this research is to take advantage of the radiation conditions in the area in order to generate electricity and then inject this energy into the medium-voltage grid in the ZAPOTILLO #1 813 primary feeder belonging to the Pindal substation. The demand for electrical energy, electrical power and per capita consumption in Zapotillo is determined, as well as its evolution in the years 2014, 2015, 2016 and 2017. The environmental and economic aspects were analyzed through profitability indicators that guarantee the economic viability and sustainability of the project.